Trace inequalities for positive operators via recent refinements and reverses of Young’s inequality - Dragomir S. S. (Special Matrices, 2018)
In this paper we obtain some trace inequalities for positive operators via recent refinements and reverses of Young’s inequality due to Kittaneh-Manasrah, Liao-Wu-Zhao, Zuo-Shi-Fujii, Tominaga and Furuichi.